Phase IIa Proof-of-Concept Evaluation of the Antiviral Efficacy, Safety, Tolerability, and Pharmacokinetics of the Next-Generation Maturation Inhibitor GSK3640254 . (6th January 2022) - Spinner, Christoph D; Felizarta, Franco; Rizzardini, Giuliano; Philibert, Patrick; Mitha, Essack; Domingo, Pere; Stephan, Christoph J; DeGrosky, Michelle; Bainbridge, Veronica; Zhan, Joyce; Dumitrescu, Teodora Pene; Jeffrey, Jerry L; et al.
Abstract: Background: GSK3640254 (GSK'254) is a next-generation human immunodeficiency virus type 1 (HIV-1) maturation inhibitor with pharmacokinetics (PK) supporting once-daily therapy. Methods: This phase IIa double-blind (sponsor-unblinded), randomized, placebo-controlled, adaptive study evaluated antiviral effect, safety, tolerability, and PK of once-daily GSK'254 monotherapy administered with food (moderate-fat meal) in HIV-1–positive, treatment-naive adults. In part 1, participants received GSK'254 10 or 200 mg for 10 days. In part 2, participants received GSK'254 40, 80, or 140 mg for 7 days, modified from 10 days by a protocol amendment to decrease potential for resistance-associated mutations (RAMs). The primary endpoint was maximum change from baseline in HIV-1 RNA. Results: Maximum changes in HIV-1 RNA of −0.4, −1.2, −1.0, −1.5, and −2.0 log10 occurred with GSK'254 10, 40, 80, 140, and 200 mg, respectively. Regardless of dosing duration, doses ≥40 mg resulted in ≥1-log10 declines in HIV-1 RNA. Plasma PK was generally dose proportional to 140 mg but non-proportional between 140 and 200 mg. Four participants in the 200-mg group developed RAMs on day 11 in part 1, 1 with phenotypic resistance. No RAMs occurred in part 2. Adverse events (AEs) were reported by 22 (65%) participants; headache was the most common (n = 4). Two non–drug-related serious AEs occurred. All AEs were of mild-to-moderate intensity, except for 2 grade 3 non–drug-related AEs in 1 participant. Conclusions: This monotherapy study established a dose–antiviral response relationship for GSK'254. No safety or tolerability concerns were noted. These results supported dose selection for the ongoing phase IIb study (ClinicalTrials.gov: NCT04493216). Clinical Trials Registration: NCT03784079. Abstract : This proof-of-concept monotherapy study of treatment-naive adults confirmed the antiviral activity of the next-generation HIV-1 maturation inhibitor GSK3640254 and established a dose–antiviral response relationship. No major safety or tolerability findings were observed, supporting the ongoing phase IIb study. Video Abstract: